Strategi Pemberdayaan Ekonomi Masyarakat Desa Melalui Agrowisata di Kabupaten Banyumas - Rahab, Rahab; Nurrahman, Rizky; Sulaiman, Adhi Iman (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
Cikidang Village is located in Cilongok Sub-district, Banyumas Regency, Central Java Province. Cikidang Village is the smallest village that attracts attention because it is located along the Purwokerto -Ajibarang provincial road and is dominated by agricultural land. The Cikidang Village Government has a short-term plan to explore the village's potential which includes natural resources, economic assets, social and cultural heritage, and human resources through the development of community-based agritourism. The medium-term plan for Cikidang Village is set out in the draft RPJMDES 2020-2025. This qualitative research involved field observations, interviews and documentation. Key informants in this research include the Village Head, Village Secretary, and General Affairs Officer of the Cikidang Village Government, as well as other stakeholders such as the Head of Bumdes, Head of Farmer Groups, Local Entrepreneurs, Community Leaders, and external parties including the Banyumas Regency Youth, Sports, Culture & Tourism Office, and Banyumas Regency small and medium business associations. The results revealed the potential of natural resources that can be developed as agro-tourism objects, while the development of the Cikidang Village rest area functions as a tourist centre that promotes local products and culture of the village. Based on stakeholder analysis shows that the participation of various parties in the agritourism development plan in Cikidang Village. Strategies to empower the community economy through agritourism in Cikidang Village are formulated in three stages, namely creating a conducive atmosphere, effective village government management, and maintaining long-term sustainability.